Pengaruh sektor pariwisata terhadap kesejahteraan masyarakat di Provinsi Daerah Istimewa Yogyakara - Hakami, Muhammad Emran (Economics, Finance, and Business Review, 2025)
This study aims to analyze the influence of the tourism sector on community welfare in the Special Region of Yogyakarta Province. The variables used in this study are the number of tourist attractions, the number of tourists, hotels, and the number of restaurants and eateries as independent variables, and the dependent variable is adjusted per capita expenditure. This study analyzed 5 districts/cities in the province of DIY in the period 2018 - 2023. The analysis method used is the panel data regression method. The test results show that the fixed effect method is the best method for estimating panel data. The results of this study indicate that the number of tourists, the number of hotels, and the number of restaurants and eateries have a positive effect on per capita expenditure while the number of tourist destinations does not affect per capita expenditure. The implication of this finding is the need for each local government to embarrass creative innovation in managing hotels, restaurants, and eateries to make Yogyakarta the main destination for tourists in Indonesia.